2020
DOI: 10.1136/bmjopen-2019-035824
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Outcomes of patients Undergoing Resection for upper gastroIntestinal cancer in AuStralian Hospitals (NOURISH): protocol for a multicentre point prevalence study

Abstract: IntroductionNutritional intervention and prevention of malnutrition is significantly important for patients with upper gastrointestinal oesophageal, pancreatic and gastric cancer. However, there is limited information regarding nutritional status, and perioperative nutritional interventions that patients receive when undergoing curative surgery.Methods and analysisPatients diagnosed with upper gastrointestinal cancer, planned for curative intent resection across 27 Australian hospitals will be eligible to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Ethics approval was obtained from The Peter MacCallum Cancer Centre Ethics Committee prior to commencement (LNR/51107/PMCC-2019). Further details of study design, participating sites, and methods are reported in the previously published study protocol [ 12 ]. Verbal consent was provided by participants and all patients received the standard dietetics care of the participating health service.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ethics approval was obtained from The Peter MacCallum Cancer Centre Ethics Committee prior to commencement (LNR/51107/PMCC-2019). Further details of study design, participating sites, and methods are reported in the previously published study protocol [ 12 ]. Verbal consent was provided by participants and all patients received the standard dietetics care of the participating health service.…”
Section: Methodsmentioning
confidence: 99%
“…Percentage weight loss was also calculated at the 3-month, 1-month, and 2-week preoperative timeframes. Clinical data were obtained from participant’s medical records, including age, sex, postcode of residence to determine metropolitan or regional/rural locality, surgery type (gastric, oesophageal, or pancreatic), tumour type, pathological tumour stage from intraoperative histopathology [ 15 ], receipt of neoadjuvant chemo/radiotherapy, surgical LOS, and surgical complications (converted into a binary variable of ‘no complications’ or ‘one or more complication’) ( Supplementary File 1 ) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nutritional Outcomes of patients Undergoing Resection for upper gastroIntestinal cancer in AuStralian Hospitals study (The NOURISH Point Prevalence Study) was conducted to investigate nutritional status and nutritional interventions received by patients undergoing UGI cancer surgery and associations with clinical outcomes, as well as health-service-level practices [ 17 ]. NOURISH is the largest study internationally to assess nutritional status in UGI cancer patients at the time of surgery using a validated assessment method [ 17 ]. The aims of this study were to determine the prevalence of malnutrition, clinically important weight loss, low muscle strength and nutrition impact symptoms.…”
Section: Introductionmentioning
confidence: 99%